Pengembangan E-Modul Gizi Balita Berbasis Canva pada Mata Kuliah Gizi Terapan - Zakiah, Azzahra; Nur Riska; Rusilanti (LPPM Universitas Negeri Jakarta, 2024)
This research aims to: 1) Develop Canva-based toddler nutrition e-module teaching materials and 2) Assess the feasibility of Canva-based toddler nutrition e-module teaching materials. This teaching material was developed using the Research and Development method with the ADDIE development model. The stages of this research consist of five stages, namely analysis, design, development, implementation and evaluation. Research data was collected using a questionnaire and analyzed descriptively qualitatively. The results of the research show that Canva-based toddler nutrition e-module teaching materials are considered